PELAS RUAS DE MARINGÁ: PLANEJAMENTO URBANO E ARBORIZAÇÃO VIÁRIA NO NOVO CENTRO DE MARINGÁ, PR, BRASIL (Terr@ Plural, 2019)
We studied the process of settlement and urban planning of the region called 'Novo Centro' in Maringá through the analysis and diagnosis of urban afforestation in its main street. Methodological procedures included two aspects: the process of development and urban planning, surveying the historical and legislative aspects from 1985 to 2018; and a survey of the street afforestation monitoring when an on-site diagnosis was made through a spreadsheet for qualitative and quantitative characterization of the trees present. The results show that the Novo Centro Maringá is subdivided into three glebes: A, B, and C, with specific occupancy patterns. Regarding afforestation, this is few diverse, with 47 tree individuals of a single species, ipê-branco, all planted on the south side of the avenue